Therapeutic Efficacy of Human Macrophage Colony-Stimulating Factor, Used Alone and in Combination with Antifungal Agents, in Mice with Systemic Candida albicans Infection - Kuhara, Tetsuya (American Society for Microbiology, 2000)
We examined the in vivo activity of human macrophage colony-stimulating factor (hM-CSF) against lethal Candida albicans infection in mice. In C. albicans-infected mice which had been immunosuppressed with cyclophosphamide, treatment with hM-CSF at a daily dose of 8 × 10(5) units/kg of body weight or greater slightly but significantly prolonged survival. Furthermore, the therapeutic efficacy of amphotericin B (AMPH-B) in infected mice was enhanced by its combined use with hM-CSF, while that of fluconazole (FLCZ) was not. The activities of peritoneal macrophages and neutrophils from mice administered hM-CSF plus AMPH-B in combination for inhibition of hyphal growth of C. albicans cells and intracellular phagocytosis and killing of the cells were greater than those of comparable phagocytic cells from control mice to which hM-CSF plus AMPH-B was not administered. These results suggest that intravenous administration of hM-CSF augments the efficacy of AMPH-B by enhancing the antifungal activities of macrophages and neutrophils. Therefore, it is expected that therapy with the combination AMPH-B and hM-CSF could improve the efficacy of AMPH-B and reduce the therapeutic dose of the antifungal drug that is required.